Polyploid Giant Cancer Cells, a Hallmark of Oncoviruses and a New Therapeutic Challenge - Herbein, Georges; Nehme, Zeina (Frontiers in Oncology, 2020)
Tumors are renowned as intricate systems that harbor heterogeneous cancer cells with distinctly diverse molecular signatures, sizes and genomic contents. Among those various genomic clonal populations within the complex tumoral architecture are the polyploid giant cancer cells (PGCC). Although described for over a century, PGCC are increasingly being recognized for their prominent role in tumorigenesis, metastasis, therapy resistance and tumor repopulation after therapy. A shared characteristic among all tumors triggered by oncoviruses is the presence of polyploidy. Those include Human Papillomaviruses (HPV), Epstein Barr Virus (EBV), Hepatitis B and C viruses (HBV, HCV respectively), Human T-cell lymphotropic virus-1 (HTLV-1), Kaposi’s sarcoma herpesvirus (KSHV) and Merkel polyomavirus (MCPyV). Distinct viral proteins, for instance Tax for HTLV or HBx for HBV have demonstrated their etiologic role in favoring the appearance of PGCC. Different intriguing biological mechanisms employed by oncogenic viruses, in addition to viruses with high oncogenic potential such as human cytomegalovirus, could support the generation of PGCC, including induction of endoreplication, inactivation of tumor suppressors, development of hypoxia, activation of cellular senescence and others. Interestingly, chemoresistance and radioresistance have been reported in the context of oncovirus-induced cancers, for example KSHV and EBV-associated lymphomas and high-risk HPV-related cervical cancer. This points toward a potential linkage between the previously mentioned players and highlights PGCC as keystone cancer cells in virally-induced tumors. Subsequently, although new therapeutic approaches are actively needed to fight PGCC, attention should also be drawn to reveal the relationship between PGCC and oncoviruses, with the ultimate goal of establishing effective therapeutic platforms for treatment of virus-associated cancers. This review discusses the presence of PGCCs in tumors induced by oncoviruses, biological mechanisms potentially favoring their appearance, as well as their consequent implication at the clinical and therapeutic level.